2008
DOI: 10.1021/ja8059396
|View full text |Cite
|
Sign up to set email alerts
|

Rh(I)-Catalyzed Direct Arylation of Pyridines and Quinolines

Abstract: A Rh(I)-catalyzed direct arylation of pyridine and quinoline heterocycles has been developed. The method provides rapid entry into an important class of bis(hetero)aryl products employing inexpensive and readily available starting materials.The pyridine and quinoline nuclei are privileged scaffolds that occupy a central role in many medicinally relevant compounds. 1 Consequently, methods for their expeditious functionalization are of immediate interest. However, despite the immense importance of transition-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
101
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(106 citation statements)
references
References 14 publications
3
101
0
2
Order By: Relevance
“…This reaction provided compound 20a with 16 O, suggesting that ortho-hydroxyl group was derived from Cu(OAc) 2 [25] Notably, the reaction under an Ar atmosphere gave the product in low yield, suggesting that molecular O 2 participates in the reoxidation of the Cu catalyst.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This reaction provided compound 20a with 16 O, suggesting that ortho-hydroxyl group was derived from Cu(OAc) 2 [25] Notably, the reaction under an Ar atmosphere gave the product in low yield, suggesting that molecular O 2 participates in the reoxidation of the Cu catalyst.…”
mentioning
confidence: 99%
“…In general, C-H functionalization proceeds via metallacycle formation by oxidative addition of transition-metal and subsequent coordination of nucleophile and reductive elimination. Recent research has revealed that nitrogen-containing functional groups such as pyridines [14][15][16], imines [17][18][19], oxazolines [20,21], and amidines [22] effectively act as directing groups for regioselective C-H functionalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2,3] This strategy efficiently avoids the disposal of stoichiometric amounts of metal waste generated from the organometallic reagent, ArM, in the traditional coupling manner. [2,3] Various transition metals have been reported as efficient catalysts for this transformation, for example, Pd, [4][5][6][7][8][9][10][11] Rh, [12][13][14][15] Ru, [16][17][18] Ir, [19,20] Cu, [21][22][23][24][25][26][27] and other transition metals. [28][29][30] The application of inexpensive, non-toxic, commercially available, and environmentally benign iron complexes as catalysts in chemical syntheses has attracted much attention.…”
mentioning
confidence: 99%
“…[*] W. Liu [4][5][6][7][8][9][10][11][12][13][14]. In the presence of DMEDA (40 mol %), the direct arylation of benzene was achieved in 66% yield (Table 1, entry 9), and this result showed that this particular diamine ligand was more efficient than others.…”
mentioning
confidence: 99%